Aggressive Periodontitis with Supernumerary Teeth: A Retrospective Study - Açikgöz, G.; Açikgõz, A.; Keskiner, I.; Türk, T.; Özden, F. (Amer Acad Periodontology, 2004)
Background: There are four key studies in the periodontology literature reporting the correlation between supernumerary teeth and aggressive periodontitis. The aim of this study is to detect such a relationship. Methods: Patients with supernumerary teeth were identified retrospectively from their orthopantomographs and were invited to the periodontology department for intraoral examination. They were then evaluated for aggressive periodontitis. The number of existing teeth, age, family histories, attachment loss, probing depths, and bleeding on probing scores were recorded. Results: Of the 5,850 subjects randomly observed among 48,000 patients, only 174 exhibited supernumerary teeth. Of these 174 subjects, only three patients were diagnosed with aggressive periodontitis. One of the patients was also suffering from Fanconi's anemia. Conclusions: Despite the similarities (aggressive periodontitis accompanied by supernumerary teeth) in the previous reports, we do not agree with the earlier results. We rather suggest that this association might be a random occurrence, rather than a biological one, although this observation should be further investigated using genetic testing.
Keywords: Periodontitis/Epidemiology; Tooth, Supernumerary/Epidemiology